PCSK9 Antagonists: Clinical Efficacy and Main Trends in the Development of New Medicines - A. A. Nekipelova; R. N. Alyautdin (Безопасность и риск фармакотерапии)
Scientific relevance. Cardiovascular diseases (CVD) are the leading cause of death worldwide. Dyslipidemia, as the pathophysiological basis of atherosclerosis, is the most important cause of CVD. Among the factors that modify this pathology, the World Health Organisation lists statins, which effectively reduce the cholesterol level. However, statin treatment compliance is not sufficient to achieve population-based lipid targets. This is a powerful stimulus for the creation of fundamentally new groups of lipid-lowering agents, in particular, antagonists of proprotein convertase subtilisin/kexin type 9 (PCSK9).Aim. The study aimed to review innovative approaches to developing a new generation of lipid-lowering agents, PCSK9 antagonists, and to evaluate the effectiveness, safety, and clinical potential of these medicines.Discussion. PCSK9 antagonists significantly increase the effectiveness of lipid-lowering therapy when combined with statins and are an effective monotherapy in patients with contraindications for statins. PCSK9 monoclonal antibodies, as well as inclisiran, have a favourable risk–benefit ratio. However, the high cost of commercially available PCSK9 antagonists limits their clinical use. A number of promising directions exist for developing new PCSK9 antagonists that have fundamentally different mechanisms of action, such as adnectins; genome editing with CRISPR/Cas9; combining small molecules with low molecular weight PCSK9 inhibitors; PCSK9 vaccines; and antisense oligonucleotides. Medicinal products from these groups are currently at various stages of preclinical and clinical development.Conclusions. Therefore, new lipid-lowering agents can be developed by synthesising high and low molecular weight PCSK9 ligands and by altering the genetic mechanisms of PCSK9 synthesis. The innovative medicines considered in this review are highly effective, and most have shown no signs of toxicity at the pre-authorisation stage.